2022
DOI: 10.1111/nmo.14439
|View full text |Cite
|
Sign up to set email alerts
|

5xFAD mice do not have myenteric amyloidosis, dysregulation of neuromuscular transmission or gastrointestinal dysmotility

Abstract: Background Alterations in gastrointestinal (GI) function and the gut‐brain axis are associated with progression and pathology of Alzheimer's Disease (AD). Studies in AD animal models show that changes in the gut microbiome and inflammatory markers can contribute to AD development in the central nervous system (CNS). Amyloid‐beta (Aβ) accumulation is a major AD pathology causing synaptic dysfunction and neuronal death. Current knowledge of the pathophysiology of AD in enteric neurons is limited, and whether Aβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(130 reference statements)
1
1
0
Order By: Relevance
“…By immunofluorescence (IF) staining, we found no Aβ in the 5XFAD colon (Fig. S2) as previously reported [47].…”
Section: Resultssupporting
confidence: 88%
“…By immunofluorescence (IF) staining, we found no Aβ in the 5XFAD colon (Fig. S2) as previously reported [47].…”
Section: Resultssupporting
confidence: 88%
“…Additionally, both Aβ and phosphorylated tau protein were observed in the ENS neurons of the colon of AD patients. In contrast, Yelleswarapu et al could not detect Aβ accumulation in the colonic MP of 5xFAD mice and GI dysmotility at 6 months of age [132]. However, while using the 5xFAD mice, our own previous studies showed Aβ depositions in the muscular layer, as well as the MP and SP of the duodenum and ascending colon [130,133].…”
Section: Involvement Of the Ens In Alzheimer's Diseasecontrasting
confidence: 64%
“…The 5×FAD transgenic mouse line carries the Swedish ( KM670/671NL ), Florida ( I716V ), and London ( V717I ) mutations of APP and the M146L and L286V mutations of PSEN1 under the control of the Thy-1 promoter. These mice represent a robust model for studying amyloidosis, with abundant Aβ accumulation in the brain at 6 months and cognitive impairment detected at 4–6 months ( Oakley et al, 2006 ; Yelleswarapu et al, 2022 ). Triple Tg (3×Tg-AD) mice overexpress APP with the Swedish K670N/M671L mutation, PSEN1 with the M146V mutation, and protein tau with the P301L mutation, establishing a robust model for studying tau pathology and amyloidosis.…”
Section: Autophagy In Pathogenesis Of Ad Animal Modelsmentioning
confidence: 99%